Growth in Malaysia's export food market: a shift-share analysis - Alias, Emmy Farha; Radam, Alias; Yeong, Pei Fen; Yacob, Mohd Rusli; Alam, Md. Ferdous (Canadian Center of Science and Education, 2014)
Agriculture sector plays an important role in the Malaysian economy. Malaysia experiences deficit in food balance of trade but some of the agricultural products such as palm oil, fisheries etc. have competitive advantage. This paper aims to examine Malaysia’s export food market growth between 1996 and 2009 using shift-share analysis. Findings show that the major export commodities from Malaysia are animal or vegetable fats and oils and their cleavage products; prepared edible fats; animal or vegetable waxes (HS 15) during the said period. The increasing growth rate of Malaysia’s exports is found in the newly industrialized countries such as China, Iran, India and Ukraine due to their increasing demand for edible oil. However, influences of the trading agreements between these countries also cannot be denied.